REPLACEMENT OF CONCENTRATE WITH MAGGOT (Hermetia illucens) ON THE EGG QUALITY OF PUREBRED CHICKENS - A. I., Septyaningrum,; Astawa, I P. A.; Suasta, I M. Suasta (Jurnal Peternakan Tropika, 2024)
The aim of this research was to gain knowledge regarding replacing concentrate with maggot on the quality of purebred chicken eggs and was carried out for 8 weeks in Candikusuma Village, Melaya District, Jembrana Regency, Bali Province. The research design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications. This research used a Completely Randomized Design (CRD) which included four treatments and four replications. Each replication consisted of four chickens aged 35 weeks, so there were 64 chickens. The four treatments are A control (breed chickens without replacing concentrate with maggots), B (3% replacement of concentrate with maggots), C (4% replacement of concentrate with maggots), D (5% replacement of concentrate with maggots). For observations of egg quality, 16 fresh eggs were taken and then broken every week to test the quality for 4 weeks. This research took variables to observe, namely egg white index, egg weight, egg yolk color, egg yolk index, egg shell thickness, and haugh unit (HU). The results of this study show that replacing concentrate with maggot on egg yolk index, egg white index, egg shell thickness, and haugh units, showed increased results in each treatment, but for egg yolk color and egg weight did not show any significant differences. from treatment A. Based on the results of this study, it can be concluded that replacing concentrate with maggot on the quality of purebred chicken eggs can increase the yolk index, white index, egg shell thickness and haugh units, and does not affect egg weight and egg yolk color.